Empiric Auto-Titrating CPAP in People with Suspected Obstructive Sleep Apnea - Drummond, Fitzgerald (American Academy of Sleep Medicine, 2010)
OBJECTIVE: Efficient diagnosis and treatment of obstructive sleep apnea (OSA) can be difficult because of time delays imposed by clinic visits and serial overnight polysomnography. In some cases, it may be desirable to initiate treatment for suspected OSA prior to polysomnography. Our objective was to compare the improvement of daytime sleepiness and sleep-related quality of life of patients with high clinical likelihood of having OSA who were randomly assigned to receive empiric auto-titrating continuous positive airway pressure (CPAP) while awaiting polysomnogram versus current usual care. METHODS: Serial patients referred for overnight polysomnography who had high clinical likelihood of having OSA were randomly assigned to usual care or immediate initiation of auto-titrating CPAP. Epworth Sleepiness Scale (ESS) scores and the Functional Outcomes of Sleep Questionnaire (FOSQ) scores were obtained at baseline, 1 month after randomization, and again after initiation of fixed CPAP in control subjects and after the sleep study in auto-CPAP patients. RESULTS: One hundred nine patients were randomized. Baseline demographics, daytime sleepiness, and sleep-related quality of life scores were similar between groups. One-month ESS and FOSQ scores were improved in the group empirically treated with auto-titrating CPAP. ESS scores improved in the first month by a mean of −3.2 (confidence interval −1.6 to −4.8, p < 0.001) and FOSQ scores improved by a mean of 1.5, (confidence interval 0.5 to 2.7, p = 0.02), whereas scores in the usual-care group did not change (p = NS). Following therapy directed by overnight polysomnography in the control group, there were no differences in ESS or FOSQ between the groups. No adverse events were observed. CONCLUSION: Empiric auto-CPAP resulted in symptomatic improvement of daytime sleepiness and sleep-related quality of life in a cohort of patients awaiting polysomnography who had a high pretest probability of having OSA. Additional studies are needed to evaluate the applicability of empiric treatment to other populations. CITATION: Drummond F; Doelken P; Ahmed QA; Gilbert GE; Strange C; Herpel L; Frye MD. Empiric auto-titrating CPAP in people with suspected obstructive sleep apnea. J Clin Sleep Med 2010;6(2):140-145.